PELESAPAN FUNGSI SINTAKSIS DALAM KALIMAT MAJEMUK BAHASA INDONESIA - Siti Sangadah; Mukhlish Mukhlish (Universitas Sarjanawiyata Tamansiswa, 2014)
This research aimed at (1) describing the kinds of syntactic functions disappeared in the compound sentences in Indonesian language, (2) describing the categories of syntax as the antecedents of the syntactic function disappearance of compound sentences in Indonesian language, and (3) describing the function appropriateness and constituent roles having co-reference relationship in the process of the syntactic function disappearance of compound sentences in Indonesian language. This research was classified as descriptive-qualitative research. The data were the compound sentences in Indonesian language including the compound and complex ones that were affected by the disappearance of syntactic functions. The sources of the data were (1) Kedaulatan Rakyat a newspaper; (2) Kartini a magazine; (3) Kafilah-Kafilah Cinta a novel; (4) Syair Panjang Aceh a novel; (6) Anak Semua Bangsa a roman; and (7) Lelaki Ikan a short-story collection. The method and technique used during the data collection process were scrutinizing and noting. Furthermore, the data analysis method and techniques used were evenly-distributed methods with direct-substance-distribution techniques, reversing techniques, disappearing techniques, and substituting techniques. The methods used to present the results of the data analysis were implemented informally and formally. The results of the research are: (1) the kinds of compound-sentence syntactic functions in Indonesian language that disappeared included: (a) the disappearance of syntactic function in compound sentences consisting of the disappearance of the subjects, predicates, and the objects, (b) the disappearance of syntactic functions in complex sentences consisting of the disappearance of the subjects only; (2) the syntactic categories as the antecedents of the compound sentence disappearance included (a) the antecedent categories found in compound sentences consisting of words and phrases, (b) the antecedent categories found in complex sentences consisting of words and phrases; (3) the function appropriateness and constituent roles having co-reference relationship in syntactic function disappearance in compound sentences in Indonesian language included (a) the function appropriateness and constituent roles of compound sentences consisted of function co-reference, role co-reference, and function and role co-reference, and (b) the function appropriateness and constituent roles of complex sentences consisted of function co-reference and role co-reference.